EVALUATION OF ANTIOXIDANT AND ANTIMICROBIAL POTENTIAL OF TWO ENDANGERED PLANT SPECIES ATROPA BELLADONNA AND MATRICARIA CHAMOMILLA - Munir, Neelma; Iqbal, Ayesha Saleha; Altaf, Imran; Bashir, Rasheeda; naz, shagufta; Saleem, Faiza; Naz, Shagufta (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Plants are the natural source of antioxidants as well as antimicrobial compounds that has great potentials in pharmaceutical industry. In the present study, two medicinal plants Atropa belladonna and Matricaria chamomilla were collected from Northern areas of Pakistan. Materials and Methods: The extracts of the collected plants were obtained by microwave assisted extraction (MAE) with changing parameters, power level and time; methanol and ethanol were solvents used during extraction. The extracts of plants were tested against different bacterial strains. Results: It was observed that ethanolic extracts of Atropa belladonna has more significant antimicrobial activity against S.aureus than E.coli. In parallel, methanolic extract of Matricaria chamomilla showed greater significant antibacterial activity against S.aureus when compared with E.coli. In comparison, ethanolic extracts of Matricaria chamomilla has shown more significant results against S. aureus than E.coli (p≤0.05). Both plants had no antibacterial activity against S.typhi. The free radical scavenging activity observed by DPPH assay, indicate that both plants have antioxidant activity at all levels of concentrations in solvent tested during the present work. However, methanolic extracts had greater antioxidant activity when compared with ethanolic extracts. Conclusion: Present study is thus helpful in highlighting present potentials for antioxidant and antimicrobial properties in the selected plants.